Praktik Pemasaran TikTok Shop Ditinjau Dari Etika Bisnis Islam - Maulana, Dudung; Ainulyaqin, MH; Achmad, LI; Misiden, Kisanda; Mamun, S (ITB AAS INDONESIA Surakarta, 2024)
This research discusses TikTok Shop marketing practices in terms of Islamic business ethics. Business ethics is the foundation of today's business because buyers and sellers do not meet face to face. The foundation of Islamic business ethics is applied in the TikTok Shop marketing strategy, emphasizing the principles of honesty, responsibility, no fraud, keeping promises, and generous service. The implication is that mutual trust is built between buyers, sellers and the TikTok online shop. This research method uses a qualitative method using a literature review study approach. Data sources come from scientific journals that are relevant to the research topic, accessed through various academic database sources (Google Scholar, Publish or Perish, Open Knowledge Maps, Moraref), official journal websites, and institutional repositories. In the results of his research, TikTok Shop marketing can make a positive contribution in safeguarding assets by providing a trading platform that is transparent, fair and in accordance with Islamic business ethics.